2010
DOI: 10.1167/iovs.10-5196
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional 1060-nm OCT: Choroidal Thickness Maps in Normal Subjects and Improved Posterior Segment Visualization in Cataract Patients

Abstract: The imaging performance of 3D 1060-nm OCT is unique, producing maps that show the variation in ChT over the entire field of view, in relation to axial length. This imaging system has the potential of visualizing a novel clinical diagnostic biomarker. Compared with 800-nm OCT, it provides superior visualization of the posterior pole in cataractous eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
165
4
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(188 citation statements)
references
References 32 publications
17
165
4
2
Order By: Relevance
“…However, considering the similarity of the normal values to those of the previous study, any bias deriving from the manual measurement is thought not to be significant. 7,12,13 In conclusion, increased choroidal thickness in patients with unilateral CSC was noted not only in the affected eyes, but also in the unaffected fellow eyes. This thickness change appears to correlate with certain angiographic features, such as choroidal vascular hyperpermeability and dilation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, considering the similarity of the normal values to those of the previous study, any bias deriving from the manual measurement is thought not to be significant. 7,12,13 In conclusion, increased choroidal thickness in patients with unilateral CSC was noted not only in the affected eyes, but also in the unaffected fellow eyes. This thickness change appears to correlate with certain angiographic features, such as choroidal vascular hyperpermeability and dilation.…”
Section: Discussionmentioning
confidence: 67%
“…Recently, three-dimensional 1060 nm OCT was employed for the measurement of subfoveal choroids. 12,13 In these studies, the normal values of subfoveal choroidal thickness were 354±111 and 315±106 mm, respectively. The authors had suspected that ethnicity or different age distributions in these studies might result in different choroidal thickness values.…”
Section: Discussionmentioning
confidence: 75%
“…Multiple studies have assessed choroidal thickness in healthy individuals using the OCT, [23][24][27][28][29][30] however, only a few have used a 1060nm system. [27][28] A recent study using 1060nm OCT to investigate the correlation between axial length and choroidal thickness in 34 healthy subjects (64 eyes) aged 19-80 years, found a mean central choroidal thickness of 315m (SD 106m), with the choroid thinnest in the nasal parafovea.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28] A recent study using 1060nm OCT to investigate the correlation between axial length and choroidal thickness in 34 healthy subjects (64 eyes) aged 19-80 years, found a mean central choroidal thickness of 315m (SD 106m), with the choroid thinnest in the nasal parafovea. 27 Other studies have also found choroidal thickness to be greatest at the fovea, with a greater reduction in thickness with eccentricity reported nasally than temporally, 23-24, 28, 30 a pattern reflected in our findings from both controls and individuals with early AMD. The mean subfoveal choroidal thickness reported has varied between studies from 225m (SD 53m), 23 to 354nm (SD 111m).…”
Section: Discussionmentioning
confidence: 99%
“…Those modalities might be expected to improve the repeatability of CT measurements; however, the current study suggests that further evaluations are needed to verify the repeatability of novel methods, particularly in the thick choroid. 6,9,22,24,25 In conclusion, CT measurement in eyes with a very thick choroid may be inaccurate. Increased CT leads to a lower interobserver compared with intraobserver repeatability, and this tendency was consistent despite the thorough peer-review process.…”
Section: Eyementioning
confidence: 93%